FINITE ELEMENT ANALYSIS ON DUAL SMALL PLATE AND SINGLE FIXATION PLATE FOR DISTAL COLLARBONE FRACTURE TREATMENT - Prabaswara, Ilham; Sonief, Achmad As’ad; Hidayati, Nafisah Arina; Anam, Khairul (International Journal of Mechanical Engineering Technologies and Applications, 2023)
Distal fractures on the collarbone are one of the most common fractures. Using internal fixation is one of the most widely used methods for treating fractures in the collarbone. A dual fixation plate for a collarbone fracture is reported to reduce reoperation due to fixation devices. In this study, the element analysis results will be presented using finite element analysis software (FEA software) for the fixation of collarbone fractures using dual plate fixation, superior plate, and anteroinferior plate. A three-dimensional model of a collarbone fracture with a fracture distance of 3 mm is used to obtain the equivalent von Mises stress value. There was no significant difference in the bending and compressive loadings on the double small plate fixation, superior plate fixation, and anteroinferior plate fixation. The von Mises stress equivalent for double small plate fixation has the most significant value compared to superior and anteroinferior plate fixation. This demonstrates that dual small plate fixation has better biomechanical properties than single plate fixation because it has better stress shielding ability and will accelerate bone healing due to the low load on the collarbone if used by an active patient.